Evolution of the Distribution and Dynamic of Microplastic in Water and Biota: A Study Case From the Gulf of Gabes (Southern Mediterranean Sea) - Ben Ismail, Sana; Costa, Elisa; Jaziri, Hela; Morgana, Silvia; Boukthir, Moncef; Ben Ismail, Mohamed Anis; Minetti, Roberta; Montarsolo, Alessio; Narizzano, Riccardo; Sammari, Cherif; Faimali, Marco; Garaventa, Francesca (Frontiers in Marine Science, 2022)
Marine plastic pollution is still a growing problem because of the continuous plastic release, its longevity and its ability to spread into all parts of the marine environment. Reliable data of drift pattern and accumulation zones is required to estimate environmental impacts on natural protected areas, spawning and nursery areas, etc. Studies concerning microplastics abundance in the Mediterranean Sea are increasing, but their occurrence in the Southern regions remains largely unexplored. In this study, microplastics (MPs) distribution, abundance, size and polymer type were investigated in surface water samples collected during Spring and Autumn 2019 EU H2020 Claim Project sampling Campaigns: 6 sites along the Gulf of Gabes (situated at Southern Mediterranean Sea) were sampled using Manta net (200µm mesh size). After that, laboratory microplastic characterization was performed. MPs polymer type was characterized using both Fourier Transformed Infrared (FT-IR) spectroscopy and μ-Raman spectroscopy. MPs (ranging between 0.3-5 mm) were found in all water samples with highly variable concentrations between seasons (Average abundance: 312887 items/Km2 and 77110 items/Km2 in Spring and Autumn respectively). A “season effect” was also observed in polymer abundance with a higher diversity of Polymers in Spring compared with Autumn samples where most of the MPs resulted to be Polypropylene and Polyethylene. Concerning biota, the presence of MPs in different species collected off the Gulf of Gabes was also examined for the first time. Frequency of fishes containing MPs in the stomach was very variable according to the species: 20 % for Scomber scombrus, 20% for Mullus surmuletus and only 6% for Sardinella aurita. Finally, a three-dimensional hydrodynamic model coupled with a Lagrangian Tracking Model to simulate the floating MPs dispersal and transport in the Gulf of Gabes were used to explain the high variability observed in MPs distribution. Numerical simulations showed that the litter distribution is strongly controlled by the hydrodynamic circulation and highlighted stranding area along mainly the Gulf of Gabes coasts.